Heat Killed Salmonella typhimurium Protects Intestine Against Radiation Injury Through Wnt Signaling Pathway. (18th June 2021) - Chen, Yuanyuan; Cao, Kun; Liu, Hu; Liu, Tingting; Liu, Lei; Qin, Hongran; Liao, Zebin; Hu, Xuguang; Li, Bailong; Liu, Cong; Cai, Jianming; Cui, Jianguo; et al.
Abstract : Gastrointestinal (GI) toxicity caused by ionizing radiation (IR) is a dose limiting factor in radiotherapy and a great threat for individual nuclear-related military missions. However, there are currently no available strategies to effectively prevent the damage on the intestine induced by IR. In the present study, the protective activity of Heat Killed Salmonella typhimurium (HKST) on intestine against IR was investigated. Through mouse intestinal organoids and whole body irradiation of mice, we found that the pretreatment with HKST significantly preserved the structure of small intestine upon IR exposure and promoted the proliferation of intestinal cells post-IR. Further study revealed that the radioprotective effects of HKST were involved in DNA damage response (DDR) signaling. Moreover, the stimulation of DDR signaling by HKST upon radiation damage was mediated by Wnt signaling, in which the inhibition of Wnt signaling diminished the radioprotective effects of HKST. To sum up, our study suggested HKST as a potential radioprotectant used for prevention of IR-induced GI toxicity.